Sophisticated Lady: Female Vocalists and Gendered Identity in the Brisbane Jazz Scene - Istvandity, Lauren (Journal of World Popular Music, 2016)
Like many popular music genres, jazz has historically been dominated by male figures, while female musicians, despite their contributions, are often overlooked. This article takes for its focus female vocalists, arguing that they frequently face compounded issues of discrimination based on gender. Contextualized in the jazz scene of Brisbane, Australia, the author describes a situation in which, reflective of historic practices, women are generally not taken as seriously as men. Further to this, vocalists, who in this scene are more likely to be female, are often compared negatively to instrumentalists in terms of knowledge and application of jazz theory and musicianship. As a result, female vocalists are ensnared by their gender and may have difficulty building a profile as respected musicians. Using autoethnographic methods, the author explores how vocalists need to carefully manage their performance of gender through a fluid approach to expressions of femininity, dependent on their performance for an audience or for other musicians.